Роль дистанційної освіти у викладанні медичної біології = The role of distance education in the teaching of medical biology - Narіychuk, Mikola Denisovich (Journal of Education, Health and Sport, 2015)
Narіychuk M. D. Роль дистанційної освіти у викладанні медичної біології = The role of distance education in the teaching of medical biology. Journal of Education, Health and Sport. 2015;5(4):259-263. ISSN 2391-8306. DOI: 10.5281/zenodo.16936 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A259-263 https://pbn.nauka.gov.pl/works/554867 http://dx.doi.org/10.5281/zenodo.16936 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 10.04.2015. УДК 373.5.016:004 РОЛЬ ДИСТАНЦІЙНОЇ ОСВІТИ У ВИКЛАДАННІ МЕДИЧНОЇ БІОЛОГІЇ The role of distance education in the teaching of medical biology М. Д. Нарійчук M. D. Narіychuk Одеське обласне базове медичне училище, м.Одеса Basic Odessa Regional Medical School Abstract This article contains material on the role of distance education in the teaching of medical biology. At the present stage, explore the use of social networking in education becomes an actual theory of social learning. The strongest factor in the success of students in education is the ability to participate in small study groups. Distance learning has a number of advantages, which give possibility to work through a lot of stuff. Keywords: distance education, continuity, communication, training. Анотація В статі міститься матеріал про роль дистанційної освіти у викладанні медичної біології. На сучасному етапі вивчення можливостей використання соціальних мереж, в освіті стає актуальною теорія соціального навчання. Найсильніший фактор успіху студентів в освіті – це здатність брати участь у невеликих дослідницьких групах. Дистанційне навчання має ряд переваг, що дають можливість самостійно опрацьовувати багато матеріалу. Ключові слова: дистанційна освіта, безперервність, комунікації, навчання. Аннотация В статье содержится материал о роли дистанционного образования в преподавании медицинской биологии. На современном этапе изучения возможностей использования социальных сетей, в образовании становится актуальной теория социальной учебы. Сильнейший фактор успеха студентов в образовании – это способность участвовать в небольших исследовательских группах. Дистанционная учеба имеет ряд преимуществ, которые дают возможность самостоятельно прорабатывать много материала. Ключевые слова: дистанционное образование, непрерывность, коммуникации, обучение.